2014
DOI: 10.1007/s12010-013-0717-x
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model for Cellulosic Biomass Hydrolysis: a Comprehensive Analysis and Validation of Hydrolysis and Product Inhibition Mechanisms

Abstract: The objective of this study is to perform a comprehensive enzyme kinetics analysis in view of validating and consolidating a semimechanistic kinetic model consisting of homogeneous and heterogeneous reactions for enzymatic hydrolysis of lignocellulosic biomass proposed by the U.S. National Renewable Energy Laboratory (Kadam et al., Biotechnol Prog 20(3):698-705, 2004) and its variations proposed in this work. A number of dedicated experiments were carried out under a range of initial conditions (Avicel® versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…The WSSE of Weibull model for previously published saccharification reactions was calculated according to the following equation [14]: …”
Section: Weighted Sum Of Square Error (Wsse) Calculationmentioning
confidence: 99%
See 3 more Smart Citations
“…The WSSE of Weibull model for previously published saccharification reactions was calculated according to the following equation [14]: …”
Section: Weighted Sum Of Square Error (Wsse) Calculationmentioning
confidence: 99%
“…A robust model is also critical to the industrial applications of the reaction because of its importance in engineering design. Various attempts have been made to model the kinetics of enzymatic lignocellulose degradation in the past [7][8][9][10][11][12][13][14]. However, the enzymatic lignocellulose degradation process involves in heterologous substrates, takes place on solid surface, is catalyzed by many synergistic enzymes and is affected by feedback inhibition.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several experimental studies have indicated that the overall rate of sugar liberation by enzymatic hydrolysis of cellulose and lignocellulosic biomass decreases significantly after an initial phase of rapid substrate depletion. A multitude of structural and physico‐chemical factors, e.g., substrate accessibility, crystallinity, substrate morphology, product inhibition, enzyme crowding, particle size, and mass‐transfer limitations due to insufficient mixing, have been previously reported to limit the rate of enzymatic hydrolysis. While the rate slow‐down is likely due to a combination of several factors, mechanistic models can be helpful in identifying the rate‐limiting phenomena.…”
Section: Introductionmentioning
confidence: 99%